#### Answer

$x^3-x^2-x-15$

#### Work Step by Step

$(x-3)(x^2+2x+5)=\\=x(x^2+2x+5)-3(x^2+2x+5)\\=(x^3+2x^2+5x)-3x^2-6x-15\\=x^3-x^2-x-15$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$x^3-x^2-x-15$

$(x-3)(x^2+2x+5)=\\=x(x^2+2x+5)-3(x^2+2x+5)\\=(x^3+2x^2+5x)-3x^2-6x-15\\=x^3-x^2-x-15$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.